Rozner, Sarah (audio interview #8 of 20) - Rozner, Sarah (b. 1892 - d. 12/?/1980); Berger Gluck, Sherna, interviewer
INTERVIEW DESCRIPTION - This is the sixteenth interview with Sarah Rozner conducted in her home. Rozner was feeling much better on this occasion than during the two previous sessions. TOPICS - family background; immigration; siblings; sex education;immigration to the US; conditions of the ship; arrival at Ellis Island; and first impressions of life in the United States; 11/20/1973